Median Nerve: Neurophysiological Parameters in Third Trimester of Pregnancy - Emir Tupković; Mediha Nišić; Sulejman Kendić; Semiha Salihović; Adem Balić; Kasim Brigić; Amra Ćatović (Biomolecules & Biomedicine, 2007)
An examination of neurophysiologic features of median nerve in third trimester of regularly controlled normal risk pregnancies is performed at the Department of Neurophysiology of Primary Health Centre in Tuzla during January / April 2006. Examined group consisted of 40 young females in third trimester of pregnancy, and average age of 25,6 +/- 4,9 years. Control group consisted of young healthy females with average age of 31,1 +/- 4,4 years. Symptoms and signs of carpal tunnel sy. (CST) had 12 patients, but diagnosis is neurophysiologically confirmed in 9 (75%) patients. In group of pregnant females without symptoms 3 (10,7%) patients showed neurophysiologic evidence of CTS. Sensory velocity of right median nerve was significantly lower in pregnant group of patients (p=0,002), but area of sensory potentials on both sides were lower in pregnant group (p<0,0001). Area of CMAP of right median nerve was significantly lower in pregnant group (p=0,0003). Significant differences in CTS group compared with control group were in sensory velocities of median nerve (left median nerve p=0,0007, right p<0,0001), and area of SNAP of both sides (left p<0,0001, right p=0,0001), but area of CMAP right (p=0,0003). In CTS group 7 females had unilateral and 5 had bilateral neurophysiological changes. Our conclusion is that neurophysiological parameters of median nerve in thirdtrimester of pregnancy are changed mainly due to high prevalence of CTS that might disturb quality of life and have psychological and physical implications on future mother. Hence, it is necessary to, continuously, pay enough attention in prevention or treatment of mentioned syndrome in this population group.